Comparison of different techniques for evaluation of cellular immunity to SARS-CoV-2 virus - Z. E. Afridonova; A. P. Toptygina; A. V. Bogolyubova; E. L. Semikina (Медицинская иммунология, 2023)
Most techniques for evaluation of T-cell immunity are laborious and unsuitable for routine laboratory diagnostics, thus encouraging researchers to look for accessible and reproducible tests. The purpose of our study is to compare three methods aimed for evaluation of cellular immune response levels to the SARS-CoV-2 viral antigens in patients who have been ill and vaccinated against a new coronavirus infection. We have examined 26 persons who experienced mild or moderate COVID-19 (group 1); 19 people vaccinated twice with Sputnik V, who did not have clinical COVID-19 (group 2); 21 subjects who had COVID-19 and were twice vaccinated with Sputnik V (group 3), and 14 persons who had COVID-19 twice (group 4). Peripheral blood mononuclear cells were isolated by gradient centrifugation. The first tested technique was performed as follows: the mononuclear cells were incubated with the S-protein of the SARS-CoV-2 virus, and stained with fluorescently labeled antibodies. The percentage of CD8highCD107a was counted by means of BD FACS Canto II flow cytometer. When assessed by the ELISpot method with “Human IFN-γ ELISpot” kit, IFNγ production was stimulated by SARS-CoV-2 S-protein, or a mixture of SARS-CoV-2 protein peptides in the “Corona-T-test” kit. There were no significant differences in the levels of CD107a expression on CD8high cells between the groups 1, 2, 3, and 4, as well as in amounts of IFNγ producers against SARS-CoV-2 S-protein when using “Human IFN-γ ELISpot” kit. Production of IFN was  significantly  lower  in  group  3  (hybrid  immunity), i.e., 317.29±19.04 pg/ml compared to groups 1 and 2 (post-infection and post-vaccination immunity), i.e., 454.95±20.32 and 470.77±26.24 pg /ml, respectively. The relative level of IFNγ -producing cells in group 2 was higher (22.34±3.77) versus 16.83±2.35 in group 1, and 15.46±1.83 in group 3, whereas the relative levels of IFNγ did not differ in these groups. Stimulation with full-length S-protein showed a significant reduction in the number of spots in group 4 (breakthrough immunity), i.e., 30.59±2.29 vs 58.97±4.47 in group 3. Stimulation with a mixture of SARS-CoV-2 peptides in group 4 vs group 3 revealed a significantly increased number of IFNγ -producing cells (86.72±7.20 versus 69.38±5.53) and higher IFNγ production (991.25±65.18 pg/ml versus 760.76±50.70 pg/ml). Appropriate relative values were as follows: 10.30±2.77 versus 8.61±2.66, and 68.10±9.41 versus 48.35±8.15, respectively. The results of three methods for evaluation of cellular immune response correlate positively with each other, but at different significance levels.